Respostas

2013-08-04T01:45:51-03:00
U) 4X² -  3X² - x + 1 - x = 0
X² - 2x +1 =0
--------------------------------------------------------
V) 3X² + 5X = -X - 9 + 2X² =
3X² - 2X² + 5X + x +9 =0
X²+ 6x + 9  =0
------------------------------------------------------------------------
  X ) 4+ X (X-4) = X
4+ X²- 4x =x 
4+X² - 4x - x = 0 
4+X² - 5x + 0 
X² - 5x+4 = 0
---------------------------------------------------------------------------------------------
 Z ) X (X + 3) - 40 =0
X²  + 3x - 40 = 0
 ESPERO TER AJUDADO !!